MODEL PEMBERDAYAAN BURUH PEREMPUAN INDUSTRI RUMAH TANGGA - Ma'ruf, Ahmad; Masmulyadi, Masmulyadi (Jurnal Ekonomi & Studi Pembangunan, 2013)
Abstract: The purposes of this study are: First, analyze and describe the characteristics of women workers who work at home industry in the province. Second, identify and analyze the strengths, weaknesses, opportunities, and constraints in the empowerment of women workers in the province. Third, exploring the various issues that support and hinder the empowerment of home industry women workers, and Fourth, develop a model of empowerment of women workers in the home industry sector in DIY. This study uses a participatory approach with the main subject of the laborers working in the home industry sector. Focus studies on industrial centers spread across DIY craft. Result of this study are: First, the deepening of the few centers that exist in the DIY industry is dynamics and different characteristics. Second,  empowerment of women workers of small industry include the social dimension, the social dimension of education and economy. Third,  women's empowerment strategy should take into account the characteristics of workers such as identity, age and duration of workers' education and work in the centers that exist in the location of this study, and Fourth, to realize the empowerment of women workers needed better support the integration of local agencies and institutions of society (civil society), the private sector and educational institutions. Abstrak: Tujuan studi ini, Pertama, menganalisis dan mendeskripsikan karakteristik buruh perempuan yang bekerja di industri rumah tangga di DIY, Kedua, mengetahui dan menganalisis kekuatan, kelemahan, peluang, dan kendala dalam pemberdayaan buruh perempuan di DIY, Ketiga,  melakukan eksplorasi terhadap berbagai isu yang mendukung dan menghambat pemberdayaan buruh perempuan industri rumah tangga, dan Keempat, menyusun model pemberdayaan buruh perempuan sektor industri rumah tangga di DIY. Studi ini menggunakan pendekatan partisipatif dengan subyek utama yaitu buruh yang bekerja di sektor industri rumah tangga. Fokus kajian pada sentra-sentra industry kerajinan yang tersebar di DIY. Hasil studi ini ada beberapa hal, yaitu: Pertama,  pendalaman terhadap beberapa sentra industri yang ada di DIY memiliki dinamika dan karakteristik yang berbeda-beda, Kedua, pemberdayaan buruh perempuan industri kecil meliputi dimensi sosial, pendidikan dan ekonomi, Ketiga, strategi pemberdayaan buruh perempuan hendaknya mempertimbangkan karakteristik seperti identitas, umur dan pendidikan dan lamanya buruh bekerja di sentra-sentra yang ada dalam lokasi kajian ini, dan Keempat untuk mewujudkan pemberdayaan buruh perempuan diperlukan dukungan keterpaduan baik instansi daerah maupun lembaga-lembaga masyarakat (civil society), swasta dan lembaga pendidikan.